Akhlak sebagai Objek Kajian Fundamental dalam Memahami Agama Islam: Tinjauan Pustaka Komprehensif - Ahmad Mahfuz; Muhammad Ihsanul Arief; Ahmad Khairiyannor (AL-FALAH: Jurnal Keislaman dan Kemasyarakatan, 2026)
In various literatures, creed (ʿaqīdah) is considered a central aspect of Islam, yet Imam al-Ghazali stated that creed is manifested through noble character. This study aims to explore the concept of akhlaq as the core of Islamic teachings by examining the perspectives of classical and contemporary scholars and its relevance in addressing modern moral challenges. Using a qualitative approach in the form of library research, the analysis was carried out through three main stages: data reduction, data presentation, and thematic-conceptual conclusion drawing. The content analysis technique was applied to scholarly journals and the thoughts of prominent scholars such as Al-Ghazali and Ibn Miskawayh (classical) and Quraish Shihab, Buya Hamka, and Syed Naquib Al-Attas (contemporary). The findings reveal that akhlaq is an inner manifestation emerging from a well-trained soul, reflecting the quality of faith and serving as a primary goal of Islamic law. Key concepts such as taqwa, ihsan, adab, and husnul khuluq form an integrative moral framework encompassing relationships with God, fellow human beings, and nature. Akhlaq plays a vital role in shaping a complete Muslim personality and a civilized society.